2020
DOI: 10.1097/xce.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

The acute vs. chronic effect of exercise on insulin sensitivity: nothing lasts forever

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…In our study, insulin sensitivity (Matsuda ISI) and insulin secretion (Disposition index) increased linearly across the PA categories at baseline. We also showed that an increase in PA during the follow-up decreased fasting and 2-h glucose levels, and increased insulin sensitivity and insulin secretion compared to participants who did not increase their PA. Several studies have reported positive effects of aerobic exercise, resistance training, and their combination on insulin sensitivity [22][23][24][25], but the results ) participants showed a decrease in fasting and 2 h glucose, and an increase in insulin sensitivity and insulin secretion compared to physically inactive participants. Physically active (PA3 or PA4) participants had increased levels of plasmalogen-cholines, lysoplasmalogencholines, polyunsaturated fatty acids, carotenoids, long chain acylcarnitines, imidazoles, bilirubins, aryl sulfates, hydroxy acids, indolepropionate, and indolelactate, and lower levels of diacylglycerols, monoacylglycerols, phosphatidylcholines, phosphatidylethanolamines, phosphatidylinositols, sphingolipids, bile acids, steroids, short-chain acyl carnitines, γ-glutamylamino acids, N-acyl-L-α-amino acids, glutamate, creatine, tyrosine, aspartate, mannose, pyruvate, and lactate than physically inactive participants.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, insulin sensitivity (Matsuda ISI) and insulin secretion (Disposition index) increased linearly across the PA categories at baseline. We also showed that an increase in PA during the follow-up decreased fasting and 2-h glucose levels, and increased insulin sensitivity and insulin secretion compared to participants who did not increase their PA. Several studies have reported positive effects of aerobic exercise, resistance training, and their combination on insulin sensitivity [22][23][24][25], but the results ) participants showed a decrease in fasting and 2 h glucose, and an increase in insulin sensitivity and insulin secretion compared to physically inactive participants. Physically active (PA3 or PA4) participants had increased levels of plasmalogen-cholines, lysoplasmalogencholines, polyunsaturated fatty acids, carotenoids, long chain acylcarnitines, imidazoles, bilirubins, aryl sulfates, hydroxy acids, indolepropionate, and indolelactate, and lower levels of diacylglycerols, monoacylglycerols, phosphatidylcholines, phosphatidylethanolamines, phosphatidylinositols, sphingolipids, bile acids, steroids, short-chain acyl carnitines, γ-glutamylamino acids, N-acyl-L-α-amino acids, glutamate, creatine, tyrosine, aspartate, mannose, pyruvate, and lactate than physically inactive participants.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported positive effects of aerobic exercise, resistance training, and their combination on insulin sensitivity [22][23][24][25], but the results with respect to insulin secretion have not been consistent across the studies. In the Diabetes Prevention Program, both decreased insulin sensitivity and insulin secretion were independently associated with the conversion to type 2 diabetes [26], but in other studies, the role of insulin secretion has remained unclear [27].…”
Section: Discussionmentioning
confidence: 97%
“…Aerobic exercise is usually the first choice of exercise prescription for treating IR [ 117 ]. However, as stated previously, performing moderate to high-intensity aerobic exercise might be contraindicated for some individuals with chronic diseases, and may not be feasible for previously sedentary, insulin resistant, obese individuals [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“… 81 Unlike an acute bout of exercise, the continual engagement in exercise elicits chronic physiological adaptations in the liver to enhance glucose metabolism and decreases insulin clearance which reduces the prevalence of peaks and nadirs in glucose concentrations. 82 Collectively, these mechanistic adaptations allow for enhanced regulation of glucose concentrations and limiting glycemic excursions thereby decreasing glycemic variability, which may be maintained for an extended period post-exercise.…”
Section: Discussionmentioning
confidence: 99%